2011
DOI: 10.1371/journal.ppat.1002021
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Satellite RNA Induces Yellow Symptoms on Tobacco by Targeting a Gene Involved in Chlorophyll Biosynthesis using the RNA Silencing Machinery

Abstract: Symptoms on virus-infected plants are often very specific to the given virus. The molecular mechanisms involved in viral symptom induction have been extensively studied, but are still poorly understood. Cucumber mosaic virus (CMV) Y satellite RNA (Y-sat) is a non-coding subviral RNA and modifies the typical symptom induced by CMV in specific hosts; Y-sat causes a bright yellow mosaic on its natural host Nicotiana tabacum. The Y-sat-induced yellow mosaic failed to develop in the infected Arabidopsis and tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
234
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(249 citation statements)
references
References 53 publications
6
234
0
9
Order By: Relevance
“…These changes include (1) variation in chlorophyll fluorescence and reduced chlorophyll content [3], (2) inhibition of photosynthetic activity [17], (3) disproportionate accumulation of photoassimilates [1,23], (4) alterations in chloroplast ultrastructure and functions [4,25], (5) downregulation of nuclear-encoded chloroplast and photosynthesis-related genes and proteins (CPRGs and CPRPs, respectively) [8,21,34,35], (6) direct binding of viral components with chloroplast factors [4,33], and (7) perturbation of photosynthesis by regulation of host miRNA expression [43].…”
Section: Introductionmentioning
confidence: 99%
“…These changes include (1) variation in chlorophyll fluorescence and reduced chlorophyll content [3], (2) inhibition of photosynthetic activity [17], (3) disproportionate accumulation of photoassimilates [1,23], (4) alterations in chloroplast ultrastructure and functions [4,25], (5) downregulation of nuclear-encoded chloroplast and photosynthesis-related genes and proteins (CPRGs and CPRPs, respectively) [8,21,34,35], (6) direct binding of viral components with chloroplast factors [4,33], and (7) perturbation of photosynthesis by regulation of host miRNA expression [43].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, antiviral silencing is considered to be highly specific and target only the virus that initially triggers the immune response (1,3,4). Silencing of specific host genes occurs when there is nearperfect complementarity between a viral siRNA and the cellular mRNA (7,8).…”
mentioning
confidence: 99%
“…All these results indicate that Y-Sat-induced symptoms are caused by the vsiRNAs-mediated silencing of CHLI. Similarly, Shimura et al [62] also revealed the molecular mechanism of the yellowing symptom induced by Y-Sat. They found that transgenic N. benthamiana plants that expressed the inverted-repeat sequence of Y-Sat also developed yellowing symptom similar to the Y-Sat-infected plants.…”
Section: Potential Action Of Vsirnas In Regulation Of Host Transcriptmentioning
confidence: 88%
“…Many cases referred to above show clearly that host plants, once invaded by virus, will activate their own RNA silencing system to target the foreign nucleic acid [8,11,12], and the virus will correspondingly express an RNA silencing suppressor to restrict the host defense system [5961]. Also, viral satRNA can utilize the host RNA silencing system to regulate the expression of certain host genes and thus induce symptoms [58,62]. Pantaleo and Burgyan [19] also pointed out that CymRSV could use an RNA silencing mechanism to control the accumulation level of satRNA, while satRNA might assist helper virus to resist the silencing-based defense system of host plants [63,64].…”
Section: Role Of Vsirnas In Balancing the Interaction Between Host Hmentioning
confidence: 99%